Preliminary study on the impact of 900 MHz radiation on human sperm: An in vitro molecular approach - Keskin, I; Karabulut, S; Kaplan, A A; Alagöz, M; Akdeniz, M; Tüfekci, K K; Davis, D L; Kaplan, S (Elsevier BV, 2024)
The use of technologies that produce and emit electromagnetic fields (EMF) is growing exponentially worldwide. The biological effects of EMF-emitting equipment, such as mobile phones and other wireless devices, have been studied in the last decade using in vitro and in vivo methods. Infertility is a growing health problem, and nearly half of cases are because of male-factor. This study investigated the direct in vitro effects of 900 MHz radiation exposure on sperm parameters, genetic status, apoptotic markers, and the PI3K/AKT signaling pathway in healthy normozoospermic men. Semen samples were divided into four groups, two control (30 min and 1 h) and two EMF exposure (30 min and 1 h). Sperm parameters (motility, progressive motility, acrosomal index, morphology), genetic status (DNA fragmentation and chromatin integrity), apoptotic markers (cytokine-c and caspase-3 expression) and the PI3K/AKT signaling pathway (phosphoinoitide 3-kinase-PI3K- and phosphorylated AKT- p-AKT-) were analysed. Sperm motility were significantly reduced in 30 min EMF exposure while a significant increase in the expression of p-AKT were observed in 1 h EMF exposure group. An increased vacuolisation, acrosomal defect, extension of subacrosomal space, uncondensed chromatin structure, apoptotic signs and disrupted axoneme were observed in both EMF groups which were not observed in the control group. Other sperm parameters (morphology and acrosomal index), genetic status, apoptotic markers and the PI3K expression rates had no significant change.
Keywords: Male; Adult; Phosphatidylinositol 3-Kinases; Young Adult; Electromagnetic Fields; Caspase 3; Sperm Motility; Humans; Apoptosis; DNA Fragmentation; Spermatozoa; Proto-Oncogene Proteins c-akt; Signal Transduction